Tinjauan Lengkung Vertikal Pada Ruas Jalan Gunung Salak KKA(Sta. 44 + 000 S/D Sta. 45 + 500) - Nizar Nizar; Ammar Fadhil; Rayyani (Fakultas Teknik - Universitas Al Muslim - Bireuen Aceh- Indonesia, 2026)
Road infrastructure plays a vital role in supporting the movement of goods and services as well as improving connectivity between regions. This study focuses on the Gunung Salak–KKA road section, specifically at STA 44+000 to STA 45+500 in North Aceh Regency. The research aims to evaluate the geometric design of the road, particularly the vertical alignment, to ensure it meets technical standards and provides safety and comfort for road users. Data collection was conducted using waterpass and GPS instruments, and further processed using Google Earth, Microsoft Excel, and AutoCAD 2007. The analysis shows that the existing road segment has a slope exceeding 10%, which does not comply with the standard specified in the Geometric Design Guidelines for Intercity Roads No. 03/BM/2018, where the maximum allowable slope is 10%. The evaluation of the vertical alignment identified four vertical curves, consisting of two convex curves and two concave curves. The findings indicate that the current road geometry requires improvement to enhance safety and service performance for traffic flow